On collapse of the inner pipe of a pipe-in-pipe system under external pressure. (1st October 2018) - Alrsai, Mahmoud; Karampour, Hassan; Albermani, Faris
Highlights: Collapse of the inner pipe of the PIP system is investigated. Using a parametric study, two collapse modes are identified and explained. An empirical expression for collapse pressure of the inner pipe is proposed. The upper and lower bounds of the collapse pressure are identified. Abstract: Collapse of the inner pipe of a pipe-in-pipe (PIP) system under external pressure is studied experimentally and numerically herein. Hyperbaric chamber test results of three PIP systems with identical inner pipes and different outer pipes are presented. It is observed that the geometric and material properties of the outer pipe affect the collapse pressure of the inner pipe. Using validated finite element analyses (FEA), a parametric study is conducted and collapse mechanisms of PIPs with various combinations of outer and inner pipes with practical range of diameter-to-thickness ratios ( D / t ) between 15 and 40 are discussed. Empirical expressions are proposed for the collapse pressure of the inner pipe ( Pci ), and its upper and lower bounds. The proposed empirical equation for Pci, is shown to agree well with the experimental results of the tested PIPs. Moreover, two distinctive modes of collapse in the inner pipe are identified and discussed.